Analisis Pendapatan dan Kelayakan Usaha Tani Padi di Kawasan Lembaga Kemajuan Pertanian Muda (MADA) Malaysia - Huda, Ikhsanul; Sitorus, Reyza Suwanto; Muhammad, Rasmuna Mazwan Binti (Universitas Galuh, 2026)
This study aims to analyze the income and feasibility of rice farming in the Muda Agricultural Development Authority (MADA) region, Malaysia. The data used is secondary data obtained from MADA annual reports, publications of the Malaysian Ministry of Agriculture, and related scientific literature. The analytical methods employed include income analysis, revenue-to-cost ratio (R/C ratio), and break-even point (BEP) analysis. The results indicate that rice farming in MADA generates relatively high revenues with positive net income after deducting production costs. The R/C ratio was found to be greater than one, signifying that rice farming is economically feasible. Moreover, the BEP analysis reveals that both production volume of 4.167 kg/ha and selling price of rice of RM 1,03/kg have surpassed the break-even point, further confirming the feasibility of the enterprise. Therefore, rice farming in the MADA area can be considered efficient and has strong prospects for future development.